The core model : a collaborative paradigm for the pharmaceutical industry and global health care - Sanchez-Serrano, Ibis (Academic Press, an imprint of Elsevier, 2019)
The Core Model: A Collaborative Paradigm for the Pharmaceutical Industry and Global Health Care develops the innovative core model, an organizational research and design paradigm and economic theory that proposes a collaborative approach to resolving global health issues and improving the productivity of drug development. The model proposes that scientific collaboration does not occur in an unstructured manner, but actually takes place within a highly structured order where knowledge is transferred, integrated and finally translated into commercial products. An understanding of this model will help solve the global pharmaceutical industrys productivity problems and address important global health care and economic issues. This book is useful to researchers, advanced students, regulators, and management in pharmaceutical industries, as well as healthcare professionals, those working in health economics, and those interested in scientific innovation processes.